Stephen Mitchell y el paradigma relacional en psicoanálisis (2014)
ABSTRACT: This paper aims to show Relational Psychoanalysis as a new paradigm within the psychoanalytic field. To do so, it is given a brief description about its origins in the U.S. context and a general review about the work of Stephen A. Mitchell: one of the most important relational authors. Some of his essential ideas are explained, such as the relational conflict model and the concept of relational matrix. In addition, some contrasts between different psychoanalytic models are presented, as well as some of theoretic and technical implications that the relational paradigm brings to psychotherapy, psychoanalysis and psychology.